Anti-platelet therapy algorithms in women - O. N. Tkacheva; T. V. Kirsanova; N. V. Latysheva (Кардиоваскулярная терапия и профилактика)
The review is focussed on the evidence base for anti-platelet therapy (APT) algorithms in women. Gender-specific features of haemostasis and thrombosis pathogenesis are emphasized. The “female” risk factors for thrombotic events include oral contraceptive use, pregnancy and post-labour period, menopause, and hormone replacement therapy. The APT role in primary and secondary cardiovascular prevention among women is analyzed. The gender-specific indications for acetylsalicylic acid therapy include pre-eclampsia, antiphospholipid syndrome, and migraine.